Full Life-Cycle Support for End-to-End Processes. - Steffen, Bernhard; Narayan, Prakash (Computer (00189162), 2007)
The article presents a means of providing full life-cycle support for end-to-end processes. This approach combines service orientation and model-driven design in a way that bridges the gap between business objectives and information technology (IT) implementations. Principals from business and development collaborate at the very beginning when the product is defined. The implementation is supported by a toolset based on the Java Application Building Center framework, which can support a variety of languages including C, Java, and JavaScript.